Pengaruh Latihan Explosive Push-up Dengan Drop and Catch Push-up Terhadap Peningkatan Daya Tahan Otot Lengan - Romdoni, Doni; Sutisna, Nana; Rustiawan, Hendra (Jurnal Keolahragaan, 2023)
The perseverance of the arm muscles that are focused on changes in the increment that comes from the impact of hazardous push-ups and drop and catch push-ups. Balebat Volleyball Club, Kawali Locale, Ciamis Regime is the exploration area. There are 20 players who are utilized as exploration objects. The exploration strategy applied is the free trial plan. The estimation apparatus utilized is push-ups. The outcomes got are: 1. Unstable push-up preparation fundamentally affects positive changes in arm muscle perseverance of Balebat Volleyball Club understudies, Kawali Locale, Ciamis Regime. 2. The drop-and-catch push-up practice fundamentally affects positive changes to the arm muscle perseverance of understudies of the Balebat Volleyball Club, Kawali Locale, and Ciamis Regime. 3. There is a massive contrast between dangerous push-ups and drop-and-catch push-ups for positive changes in arm muscle perseverance. Conclusion. There are contrasts in certain progressions from the impact of hazardous push-ups and drop and catch push-ups on muscle perseverance information on the ITH segment.